Blossomlab International Sdn Bhd / Amirul Amin Roslan - Roslan, Amirul Amin (Faculty Of Chemical Engineering, 2021)
Internship has been used as an alternative for undergraduates to deeply understand the flow of work in an actual industrial field. Internship is also known as a period of industrial training that has been offered by organizations for a limited time. It is also an alternative for students and graduates to learn relevant skills such as communicating between your co-workers, understands the flow of work in a particular field, managing to achieve one's organization mission and vision and acknowledge the importance of rules and regulations within the industry. Some internships programmes are usually handled by third-party organizations that recruit interns on behalf of industry groups. Internships are utilised to see if the intern is still interested in the field after gaining real-world experience. An internship can also be used to develop a professional network that can help with letters of recommendation or lead to future job chances. Bringing an intern on as a full-time employee has the advantage of requiring little to no training because they are already familiar with the company. Internships allow current college students to participate in an area of their choice and gain hands-on experience in a potential vocation, preparing them for full-time employment after graduation. As per my internship period, I have choose Blossom Lab International Sdn Bhd to fulfil my last semester projects. In this report I have also included the summary of the company information and my throughout progress during the industrial training period.